1986
DOI: 10.1002/jor.1100040312
|View full text |Cite
|
Sign up to set email alerts
|

Bone ingrowth into weight‐bearing porous fiber titanium implants. Mechanical and biochemical correlations

Abstract: Bone ingrowth into weight-bearing porous fiber Ti-6Al-4V implants in rat tibias was assessed for the amount, composition, and mineralization rate 3, 12, and 26 weeks after implantation. The data were compared with the ipsi- and contralateral metaphyseal controls and related to the ultimate bending stresses of the distal bone/implant interfaces. From the 3rd to the 12th week there was rapid bone ingrowth and also marked decline in mineralization rate of the ingrowing bone. After 12 weeks the implants were macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Most OS patients are treated by a closely timed combination of chemotherapy (often CDP) and tumor resection, in many cases followed by a type of limb salvage procedure including DO (Cure Search: Children’s Oncology Group/COG). Surgical reconstruction, DO, and endoprostheses are also used commonly, yet these patients continue to be at risk for postoperative complications relating to inherent poor bone repair outcomes 1-4, 10, 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most OS patients are treated by a closely timed combination of chemotherapy (often CDP) and tumor resection, in many cases followed by a type of limb salvage procedure including DO (Cure Search: Children’s Oncology Group/COG). Surgical reconstruction, DO, and endoprostheses are also used commonly, yet these patients continue to be at risk for postoperative complications relating to inherent poor bone repair outcomes 1-4, 10, 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy followed by surgery with additional adjuvant chemotherapy has become a common treatment approach (Cure Search/COG). However, since CDP is extensively used for the treatment of OS, we believe the effects of CDP treatment on direct bone regeneration need further study 10-12 . Therefore, we tested the effects of two CDP dosing regimens on bone regeneration in a mouse model of distraction osteogenesis (DO) 13-16 .…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation for the absence of increased mechanical strength by the relatively higher bone ingrowth and active mineralizing surfaces at HA-coated implants in press fit might be that maturation of bone was still incomplete. Recently, Barth et al (1986) reported that strength of the interface depends on the maturation of the mineralized bone matrix of the ingrown trabeculae. In the present study the ingrown bone was still immature.…”
Section: Discussionmentioning
confidence: 99%
“…The dose and regimen were selected to be as similar as possible to current clinical use (2,7,13,14,17,23,26,29). The weights of the animals were monitored and the levels of blood urea nitrogen (BUN) were checked, …”
Section: Graft Handling and Experimental Designmentioning
confidence: 99%